(untitled) (Revista Iberoamericana de Bioética, 2017)
There are numerous and varied pathologies that can lead to a state of terminal illness, provoking numerous bioethical dilemmas that are inherent and specific to each circumstance. The objective of the present work has been to provide a current and useful analysis that can help to understand the main bioethical problems, from the perspective of biolaw that must be solved in the inevitable path towards the end of life that any terminal illness implies. The methodology used included a study of bibliographic documentation in the main databases of interest in bioethics. It can be concluded that the biolaw is a very useful tool that helps health care professionals and relatives when it comes to the analysis and decision making regarding a terminal illness. Independently of medical practice based on protocols and scientific knowledge, it is necessary to ensure that not everything that can legally be carried out is accepted in the field of biolaw.